2022
DOI: 10.3390/cancers14061390
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Fasting Synergizes with Solid Cancer Therapy by Boosting Antitumor Immunity

Abstract: Short-term fasting (STF), using a low caloric, low protein fasting mimicking diet (FMD), appears to be a promising strategy to enhance chemotherapy-based cancer efficacy, while potentially alleviating toxicity. Preclinical results suggest that enhanced tumor immunity and decreased growth signaling, via lowering of circulating insulin and insulin growth factor 1 (IGF-1) levels form the potential underlying mechanisms. STF may boost anti-tumor responses by promoting tumor immunogenicity and decreasing local immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…A comparative cell death analysis was simultaneously performed on normal HEK-293 cells ( Figure 5 B). Data curated from wet-lab experiments ensure that short-term exposure to a chemotherapeutic drug itself could not inhibit normal cells’ reproducibility because of their differential stress response under starvation [ 2 , 13 ]. Studies reported on metformin under nutrient restriction [ 41 , 44 ] also suggest that dietary restriction imposes additional toxicity over oxidative phosphorylation inhibition by metformin and thus implicates a “dual-whammy” effect on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative cell death analysis was simultaneously performed on normal HEK-293 cells ( Figure 5 B). Data curated from wet-lab experiments ensure that short-term exposure to a chemotherapeutic drug itself could not inhibit normal cells’ reproducibility because of their differential stress response under starvation [ 2 , 13 ]. Studies reported on metformin under nutrient restriction [ 41 , 44 ] also suggest that dietary restriction imposes additional toxicity over oxidative phosphorylation inhibition by metformin and thus implicates a “dual-whammy” effect on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, for the first time, we conceptualize using short-term fasting-induced autophagy to control (ACHN) renal carcinoma growth and counteract the previously reported nephrotoxic effect on normal HEK-293 cells. The following treatment not only controls cancer cell proliferation but also minimizes its cytotoxic potential against HEK-293, possibly through normal cells’ differential stress responses followed by immunomodulatory effects [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 234 Preclinical studies have shown that STF, which serves as an adjunct to various cancer treatments, may bolster antitumor immunity by attenuating immunosuppressive conditions and amplifying CD8 + T-cell cytotoxicity. 235 For example, an experimental study of non-small cell lung cancer demonstrated that STF sensitized cancer cells to anti-PD-1 therapy. The antitumor efficacy of combination therapy was achieved by inhibiting IGF-1-IGF-1R signaling in cancer cells, boosting the intratumoral CD8 cell: Treg ratio in the TME.…”
Section: Potential Role Of Dietary Factors In Cancer Treatmentmentioning
confidence: 99%
“…A number of preclinical studies have documented beneficial effects of various forms of caloric restriction on slowing cancer growth and metastatic potential and enhancing anticancer treatments as reviewed recently [12,13,14 ▪▪ ,15 ▪ ,16 ▪▪ ,17]. Thus, in a triple-negative breast cancer mouse model, caloric restriction before or after intramammary tumor cell injection reduced tumor growth, with chronic caloric restriction (20%) being more effective than caloric cycling (70% caloric restriction for 4 out of 14 days) [18 ▪▪ ].…”
Section: Effects Of Caloric Restriction In Preclinical Cancer Modelsmentioning
confidence: 99%
“…This refers to the changes induced in the nutrient sensing systems AMPK, mTORC1, and the NAD + /NADH ratio and the resulting effects, including autophagy, mitophagy, DNA repair, and antioxidative capacity as well as the sustained dependence on glucose and high proliferation in malignant cells while during caloric restriction, normal cells switch to lipid metabolism and reduced proliferation. Published as well as still recruiting clinical trials on the interactions of caloric restriction and cancer treatments have been reviewed by several authors [12,13,14 ▪▪ ,16 ▪▪ ,17,30,31 ▪ ,32 ▪▪ ]. All trials included mainly well nourished cancer patients and studied the effects of 1–3 days of complete fasting or 3–5 days of different versions of low-calorie fasting-mimicking diets supplying 600–1200 kcal on day 1 and 200–700 kcal on following days.…”
Section: Reviews On Clinical Trials In Cancer Patientsmentioning
confidence: 99%